Teachers’ Performance and Students’ Learning Outcome in the Division of Cavite Province, Philippines (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
The paper aimed to correlate the teachers’ performance and learning outcomes on grade 10 students’ first periodic test and the teachers' Performance as assessed by headteachers and students in relationships with the knowledge of the subject matter and pedagogical approaches such as constructivism, collaborative, integrative, inquiry-based and reflective approaches. The respondents were the schools offering the same strands on Information and Communications Technology, Cookery and Wellness Massage located in North Cluster, Division of Cavite Province in the Philippines. As to the knowledge of the subject matter and pedagogical approaches, the teachers' Performance was outstanding as assessed by headteachers. Amongst the pedagogical approaches, the integrative approach obtained the highest meanwhile. The reflective approach got the lowest mean.  The data were analyzed with the descriptive method and documentary analysis on teachers’ performance and learning outcomes on students’ first periodic tests. These were also the means of obtaining the data requirements of this research. The findings revealed that the teachers' Performance was highly satisfactory as assessed by students. Amongst the pedagogical approaches, constructivism approach acquired the highest mean while reflective approach got the lowest mean. Moreover, there is a significant difference on teachers' Performance as assessed by headteachers and by students, and there are a significant relationship and weak positive correlation on teachers' Performance on learning outcomes of students' first periodic test and on the assessments of students as to knowledge of the subject matter and pedagogical approaches except for reflective approach which has a very weak positive correlation.